Engaging Nonresident Fathers: Exploring Collaborative Competencies in Support of Family-Centered Practice. (November 2021) - Cryer-Coupet, Qiana R.; Stokes, McKenzie N.; Lemmons, Brianna P.; Dorsey, Marquitta
Social service providers in a variety of sectors have struggled to consistently engage nonresident fathers in service provision. A growing body of research indicates that practitioner characteristics and attitudes may help increase retention and engagement among this group of men. These findings coincide with recent mandates from federal policy makers to increase engagement of nonresident fathers in family-centered practice approaches. A central tenet of interest within this framework is the family–professional relationship. Using a collaborative competencies model, the current study seeks to advance this line of research by investigating practitioners' perceptions of their preparedness to engage nonresident fathers. Semi-structured qualitative interviews were completed with 20 social service practitioners who have experience working with nonresident fathers. A directed content analysis revealed key aspects of intrapersonal, interpersonal, and professional collaborative competencies that practitioners believe are important to facilitate meaningful father engagement. Implications for practice and future research regarding effective social work practice with nonresident fathers are discussed.